2014
DOI: 10.1371/journal.pgen.1004289
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Protein QKI Suppresses Cancer-Associated Aberrant Splicing

Abstract: Lung cancer is the leading cause of cancer-related death worldwide. Aberrant splicing has been implicated in lung tumorigenesis. However, the functional links between splicing regulation and lung cancer are not well understood. Here we identify the RNA-binding protein QKI as a key regulator of alternative splicing in lung cancer. We show that QKI is frequently down-regulated in lung cancer, and its down-regulation is significantly associated with a poorer prognosis. QKI-5 inhibits the proliferation and transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
231
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(250 citation statements)
references
References 71 publications
18
231
0
1
Order By: Relevance
“…The suppression of QKI, as may be induced by DNA methylation in the QKI promoter region (29), has been implicated in numerous cancer types (8,30,31). In addition, miR-574-5p has been indicated to affect the regulation of QKI.…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of QKI, as may be induced by DNA methylation in the QKI promoter region (29), has been implicated in numerous cancer types (8,30,31). In addition, miR-574-5p has been indicated to affect the regulation of QKI.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative exon 12 encodes 48 amino acids within the C-terminal proline-rich region (PRR). It has previously been suggested that increased expression of the long isoform containing exon 12 promotes cell proliferation during tumorigenesis (25), whereas the short isoform inhibits cell growth (26). To further investigate the mechanism by which the Notch signaling pathway is altered, Numb expression was investigated in three pairs of cervical squamous cell carcinoma and adjacent histologically normal tissues.…”
Section: Deregulation Of Numb Expression In Cervical Cancermentioning
confidence: 99%
“…The RNA-binding protein Quaking (QKI) as a critical regulator of splicing in lung cancer is frequently down-regulated [4] . QKI-5 regulates the alternative splicing of NUMB through binding to two RNA elements of NUMB pre-mRNA, which in turn suppresses cell proliferation and blocks the activation of the Notch signaling pathway.…”
Section: Roles In Regulation Of Cell Proliferation and Migrationmentioning
confidence: 99%
“…QKI-5 regulates the alternative splicing of NUMB through binding to two RNA elements of NUMB pre-mRNA, which in turn suppresses cell proliferation and blocks the activation of the Notch signaling pathway. The reduced QKI abundance is strongly associated with poorer prognosis [4] , and low-level nuclear QKI in non-small cell lung cancer (NSCLC) is an independent prognostic factor for disease-free survival [5] . Another study has demonstrated that RNA binding motif protein RBM5 and its homologous RBM6/10 antagonistically regulate NUMB exon 9 alternative splicing to control tumor cell proliferation and xenograft tumor growth [6] .…”
Section: Roles In Regulation Of Cell Proliferation and Migrationmentioning
confidence: 99%